The Effect Of Product Quality, Price, And Service On Consumer Satisfaction Of Shopee Application Users In Medan City - Filbert Filbert; Michelle Michelle; Mas Intan Purba; Nurul Wardani Lubis (Cakrawala Repositori IMWI, 2024)
The purpose of this study was to determine the effect of price on consumer satisfaction of Shopee application users in Medan City. Today, the development of e-commerce has influenced people's lifestyles, allowing online shopping with convenience. Shopee as an e-commerce platform continues to grow, but it is important to understand customer expectations and fulfill their needs. This research explores the factors that influence e-commerce service quality and how to improve the shopping experience. This study combines the theories of customer satisfaction and service quality using Shopee Visitor Population Data 2022 in Medan City with a sample of 99. The results showed that product quality, price, and service together contribute positively and significantly to the consumer satisfaction of Shopee application users. This shows that Shopee can increase the level of customer satisfaction by focusing on product quality development, effective price management, and continuous application update efforts.